I was a stranger [videorecording (DVD)] - Andersen, Brandt, 1977-; Elmasri, Yasmine; Mahayni, Yahya; Sy, Omar, 1978-; Bakri, Ziad, 1980-; Markoulakis, Constantine; Beghe, Jason, 1960-; Samman, Ayman; Daoud, Massa (Angel Studios, 2026)
A doctor, a soldier, a smuggler, a father, and a captain. Each one on their own journey. Their paths cross in a desperate pursuit of safety and belonging. Set across four countries and inspired by real stories from the frontlines of the refugee crisis, this sweeping drama captures the heartbreak, danger, and fragile beauty of those who dare to start over when the world gives them nothing.